2016
DOI: 10.1111/aos.13259
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of retinal function using chromatic pupillography in retinitis pigmentosa and the relationship to electrically evoked phosphene thresholds

Abstract: Chromatic pupillography demonstrated a significant decrease in outer retinal photoreceptor responses but a persisting and disinhibited intrinsic photosensitive retinal ganglion cell function in advanced RP. These phenomena may be useful as an objective marker for the efficacy of any interventional treatment for hereditary retinal diseases as well as for the selection of suitable patients for an electronic retinal implant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…Retinitis pigmentosa (RP) is an inherited retinal degenerative disease with the progressive loss of photoreceptors, which leads to the deterioration of retinal function and morphology [1]. Mutation in specific genes that encode proteins participating in visual phototransduction is the primary cause of the death of photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…Retinitis pigmentosa (RP) is an inherited retinal degenerative disease with the progressive loss of photoreceptors, which leads to the deterioration of retinal function and morphology [1]. Mutation in specific genes that encode proteins participating in visual phototransduction is the primary cause of the death of photoreceptors.…”
Section: Introductionmentioning
confidence: 99%
“…16,29 On the other hand, the threshold for eliciting phosphenes by TES is elevated significantly in eyes with RP. 10,11,18 Several studies have shown that 5 to 10 times stronger currents were needed to evoke a phosphene by TES in RP patients than in the controls. 10,18 The reason for this has not been definitively determined but a degeneration of the RGCs has been suspected 18 because optic atrophy is one of features of the fundus of RP patients.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,18 Several studies have shown that 5 to 10 times stronger currents were needed to evoke a phosphene by TES in RP patients than in the controls. 10,18 The reason for this has not been definitively determined but a degeneration of the RGCs has been suspected 18 because optic atrophy is one of features of the fundus of RP patients. In addition, some histologic studies have confirmed a reduction in the number of RGCs in the retina and axons in the optic nerve of eyes of RP patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Several clinical studies have successfully used chromatic pupillometry to assess the function of rods, cones, and ganglion cells in various diseases including RP. [15][16][17][18][19][20] However, because full-field light stimuli were used, with a stimulus size that was equal to or larger than 90°, the pupillometry measurements reflect the massed response from the whole retina and cannot be used to assess focal changes in photoreceptor function.…”
Section: Introductionmentioning
confidence: 99%